I need to show that the covariance and autocorrelation functions of a stationary time series are symmetric around zero. From my understanding, this entails $$ \gamma(h) = \gamma(-h) $$ $$ \rho(h) = \rho(-h) $$ I also know that $$ \gamma(s, t) = cov(Y_s, Y_t) = E\{(Y_s-\mu_s)(Y_t-\mu_t)\} $$ $$ \rho(s,t) =\frac{\gamma(s,t)}{\{\gamma(s,s)\gamma(t,t)\}^{1/2}} $$ and that for a stationary process specifically the mean $\mu_t$ is constant and $\gamma(s,t)$ depends only on $t - s$. However, I am unsure of where to go with said information aside from $$ \gamma(t, t+h) = \gamma(0,h) = \gamma(h,0) = \gamma(0, -h) $$ but I'm pretty sure that doesn't really constitute as showing something.

I also need to consider a stationary bivariate time series $\{(X_t,Y_t)\}_{t\in\mathbb{Z}}$, defining the cross-covariance function as $\gamma_{XY}(s,t) = cov(X_s, Y_t)$ , and state whether this is also symmetric around zero, but I figure I'd have a better grasp on that if I understood the logic of the first part.


Based on @ChristophHanck's comment, I've determined the covariance calculation as follows: $$ \gamma(h)=E\{(Y_t-\mu_t)(Y_{t+h}-\mu_t)\}=E[Y_tY_{t+h}]+E[-Y_t\mu_t]+E[-Y_{t+h}\mu_t]+E[\mu_t^2] $$ $$ =E[Y_tY_{t-(-h)}]+E[-Y_t\mu_t]+E[-Y_{t-(-h)}\mu_t]+E[\mu_t^2]=E\{(Y_t-\mu_t)(Y_{t-(-h)}-\mu_t)\} = \gamma(-h) $$ However, I am unsure of how to proceed with this knowledge into the correlation function unless I can assume that $\gamma(s,s)$ and $\gamma(t,t)$ are constants $\sigma_s^2$ and $\sigma_t^2$ respectively and just use this variance solution as the primary driving force in the matter.

  • $\begingroup$ Hint in furtherance of Christoph Hanck’s answer: Stationarity means, among many other things, that all the random variables in the time series have the same mean. $\endgroup$ Sep 29, 2018 at 11:40

1 Answer 1


Take a zero mean process for simplicity.

Then, $\gamma_j=E(Y_tY_{t-j})$. Under stationarity, the point in time at which we compute the expectation does not matter. Hence, we may add $j$ to each time index to get $$ \gamma_j=E(Y_{t+j}Y_{t})=E(Y_{t}Y_{t+j})=E(Y_{t}Y_{t-(-j)})=\gamma_{-j} $$

  • $\begingroup$ Thanks for the response! Using that logic with a mean I guess would lead to $$ \gamma(h) = E\{(Y_t-\mu_t)(Y_{t+h}-\mu_t)\} = E(Y_t Y_{t+h}) + E(-Y_t \mu_t) + E(-Y_{t+h} \mu_t) + E(\mu_{t}^2) = E(Y_t Y_{t-(-h)}) + E(-Y_t \mu_t) + E(-Y_{t-(-h)} \mu_t) + E(\mu_{t}^2) = E\{(Y_t-\mu_t)(Y_{t-(-h)}-\mu_t)\} = \gamma(-h) $$ $\endgroup$
    – strwars
    Sep 28, 2018 at 21:41
  • $\begingroup$ I'm still a bit lost on the correlation and bivariate to be honest though. Do I just assume the standard deviations of $Y_s$ and $Y_t$ are constants as $\sigma_s$ and $\sigma_t$ respectively and use the fact that $\gamma(h) = \gamma(-h)$ to show $\rho(h) = \rho(-h)$ ? I greatly appreciate your assistance on this question @ChristophHanck ! $\endgroup$
    – strwars
    Sep 29, 2018 at 7:26

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.